SDGs-Based Green Curriculum Design in Secondary Schools: Analysis of Assessment and Needs - Mutiara Felicita Amsal; Dony Darma Sagita (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2026)
The integration of sustainability into education has become an urgent need in response to the global environmental crisis. This study aims to analyze teachers’ assessments, identify integration needs, and design a Sustainable Development Goals (SDGs)-based Green Curriculum model for senior high schools in West Sumatra. This study employed a mixed-methods approach with a sequential explanatory design. The research subjects comprised 10 public and private senior high schools, involving 102 teachers and 312 students. Data were collected through questionnaires, interviews, focus group discussions, observations, and document analysis. The findings revealed that teachers’ support for the Green Curriculum was categorized as high (82.1%), whereas students’ achievement was categorized as moderate (58.4%), with the main weakness found in their conceptual understanding of the SDGs, with an average score of 49.8%. The findings indicate a gap between structural support and the internalization of sustainability-oriented learning. The primary needs identified include strengthening authentic assessment, integrating the SDGs into school subjects, improving teachers’ competencies, and enhancing school policy support. This study produced a conceptual model of an SDGs-based Green Curriculum that is integrative, contextual, and transformative. The proposed model contributes to the achievement of SDG 4 and SDG 13 within the context of secondary education in Indonesia.